2023
DOI: 10.1371/journal.pone.0282369
|View full text |Cite
|
Sign up to set email alerts
|

Quality analysis of genomic DNA and authentication of fisheries products based on distinct methods of DNA extraction

Abstract: Molecular genetic techniques are an effective monitoring tool, but high-quality DNA samples are usually required. In this study, we compared three different protocols of DNA extraction: NaCl (saline); phenol-chloroform and commercial kit (Promega)—from three biological tissues of five individuals of Lutjanus purpureus under two methods of storage. The evaluated items included DNA concentration and purity, processing time and cost, as well as the obtaining of functional sequences. The highest average values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The authors assessed the quality of the DNA obtained from four tissues of two vertebrate species and found that the highest DNA yields were consistently obtained with one of the kits but different ones produced a better DNA quality, in terms of purity and fragmentation. In the tests carried out by Lutz et al (2023), three extraction methods were tested on several fish tissues and the results are in contrast with those found by Shuttleworth and Oosthuizen (2022) and Oduoye et al (2020), who also tested several isolation methods in fishes from different species. These marked differences highlight the need of a thorough testing and optimization of the DNA preservation and isolation method on every CKMR study.…”
Section: Isolation Of High Quality Dnamentioning
confidence: 65%
See 1 more Smart Citation
“…The authors assessed the quality of the DNA obtained from four tissues of two vertebrate species and found that the highest DNA yields were consistently obtained with one of the kits but different ones produced a better DNA quality, in terms of purity and fragmentation. In the tests carried out by Lutz et al (2023), three extraction methods were tested on several fish tissues and the results are in contrast with those found by Shuttleworth and Oosthuizen (2022) and Oduoye et al (2020), who also tested several isolation methods in fishes from different species. These marked differences highlight the need of a thorough testing and optimization of the DNA preservation and isolation method on every CKMR study.…”
Section: Isolation Of High Quality Dnamentioning
confidence: 65%
“…rate of fragmentation, concentration and rate of contaminants, respectively) showing that it is highly dependent on the tissue processed, the storage conditions and the species [e.g. (Silva et al, 2019;Martincováand Aghova, 2020;Lutz et al, 2023)]. Martincovaá nd Aghová (2020), tested 12 different DNA extraction methods from eight manufacturers, including some the most widely used commercial silica membrane-based kits.…”
Section: Isolation Of High Quality Dnamentioning
confidence: 99%
“…The SDS-based DNA extraction method has been widely employed for a wide range of environmental samples, plant and animal tissues, and clinical specimens. The principle of this method relies on using SDS to break organisms' membranes, using phenol/chloroform/isoamyl alcohol to degrade non-DNA molecules, and using isopropanol to precipitate DNA [10][11][12]. However, the SDS-based method is not considered to be suitable for POCT because it is a complicated procedure with multiple steps that requires bulky equipment.…”
Section: Introductionmentioning
confidence: 99%